Metschnikowia pulcherrima and Lachancea thermotolerans Killer Toxins: Contribution to Must Bioprotection - Fatima El Dana; Vanessa David; Mohammad Ali Hallal; Raphaëlle Tourdot-Maréchal; Salem Hayar; Marie-Charlotte Colosio; Hervé Alexandre (Foods)
The spoilage of wine caused by Brettanomyces bruxellensis and Hanseniaspora uvarum poses a significant challenge for winemakers, necessitating the development of effective and reliable strategies to control the growth of these yeasts, such as grape must bioprotection. Despite evidence that certain microorganisms can inhibit the growth of Brettanomyces bruxellensis and Hanseniaspora uvarum, the specific mechanisms driving this inhibition remain unclear. The primary objective of this study is to elucidate the underlying mechanisms responsible for this inhibitory effect. We analyzed one Metschnikowia pulcherrima (Mp2) and two Lachancea thermotolerans (Lt29 and Lt45) strains, all of which demonstrated significant killing and inhibitory effects on Brettanomyces bruxellensis (B1 and B250) and Hanseniaspora uvarum (Hu3137) in synthetic must at pH 3.5 and 22 °C. The effectiveness of these two strains exhibited varying inhibition kinetics. The strains were monitored for growth and metabolite production (L-lactic acid, ethanol, and acetic acid) in both single and co-cultures. The low levels of these metabolites did not account for the observed bioprotective effect, indicating a different mechanism at play, especially given the different growth profiles observed with added L-lactic acid and ethanol compared to direct bioprotectant addition. Following the production, purification, and quantification of killer toxins, different concentrations of toxins were tested, showing that the semi-purified Mp2Kt, Lt29Kt, and Lt45Kt toxins controlled the growth of both spoilage yeasts in a dose-dependent manner. These bioprotectant strains also showed compatibility with Saccharomyces cerevisiae in co-cultures, suggesting their potential use alongside commercial starter cultures.